The Detrimental Impact of Maladaptive Personality on Public Mental Health: A Challenge for Psychiatric Practice - Hengartner, Michael Pascal (Frontiers in Psychiatry, 2015)
Experts in personality psychology and personality disorders have long emphasised the pervasive and persistent detrimental impact of maladaptive personality traits on mental health and functioning. However, in routine psychiatric practice maladaptive personality is readily ignored and personality traits are seldom incorporated into clinical guidelines. The aim of this narrative review is to outline how pervasively personality influences public mental health and how personality thereby challenges common psychiatric practice. A comprehensive search and synthesis of the scientific literature demonstrates that maladaptive personality traits and personality disorders, in particular high neuroticism and negative affectivity, first, are risk factors for divorce, unemployment and disability pensioning; second, relate to the prevalence, incidence and co-occurrence of common mental disorders; third, impair functioning, symptom remission and recovery in co-occurring common mental disorders; and fourth, predispose to treatment resistance, non-response and poor treatment outcome. In conclusion, maladaptive personality is not only involved in the development and course of mental disorders, but also predisposes to chronicity and re-occurrence of psychopathology and reduces the efficacy of psychiatric treatments. The pernicious impact of maladaptive personality on mental health and functioning demands that careful assessment and thorough consideration of personality should be compulsory in psychiatric practice.